2014
DOI: 10.3346/jkms.2014.29.1.32
|View full text |Cite
|
Sign up to set email alerts
|

Human Papillomavirus Prevalence and Genotype Distribution among HIV-Infected Women in Korea

Abstract: The epidemiology on human papillomavirus (HPV) among human immunodeficiency virus (HIV)-infected women in Korea is not well established. A retrospective study was conducted to determine the prevalence and genotype distribution of HPV infection among HIV-infected women in Korea. HPV DNA genotype and cervical cytology were examined in 60 HIV-positive women and 1,938 HIV-negative women. HPV genotypes were analyzed by using a HPV DNA chip. HIV-infected women had higher prevalence of high-risk HPV (hr-HPV) infectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…The proportion of multiple carcinogenic HPV types was even higher (50%, 8/16) among women with CIN2 or worse lesion. This high rate of multiple HPV infections (consistent with the rates of 12%-87.5% in previous studies in HIV-infected populations), confounds the measurement of genotype-specific fractions attributable to individual cervical disease categories [ 13 , 15 , 22 ]. A higher prevalence of multiple HPV types may be due to different reasons, including higher persistence and lower clearance of HPV in the setting of HIV infection, continued sexual exposure to novel HPV types, reactivation of latent HPV during periods of severe immune-suppression, or may be due to high relative analytical sensitivity of the PCR assay.…”
Section: Discussionsupporting
confidence: 55%
“…The proportion of multiple carcinogenic HPV types was even higher (50%, 8/16) among women with CIN2 or worse lesion. This high rate of multiple HPV infections (consistent with the rates of 12%-87.5% in previous studies in HIV-infected populations), confounds the measurement of genotype-specific fractions attributable to individual cervical disease categories [ 13 , 15 , 22 ]. A higher prevalence of multiple HPV types may be due to different reasons, including higher persistence and lower clearance of HPV in the setting of HIV infection, continued sexual exposure to novel HPV types, reactivation of latent HPV during periods of severe immune-suppression, or may be due to high relative analytical sensitivity of the PCR assay.…”
Section: Discussionsupporting
confidence: 55%
“…This study reports for the first time the comparative prevalence and genotype distribution of HPV among HIV-1 seropositive and seronegative women in Ghana. Findings from research conducted mainly in developed countries and few studies across Africa have shown a higher prevalence of HPV infection (any HPV, hr.-HPV, multiple HPV) among HIV-1-seropositive compared with HIV-seronegative women [ 7 , 35 37 ]. In Ghana as elsewhere, HIV-1 seropositive women were significantly more frequently infected with HPV, and twice more likely to have high-risk and multiple HPV genotypes.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of human papilloma virus (HPV) infection, which causes cervical cancer, is also high among Korean women with HIV. Given that the high-risk HPV genotype which often causes cervical cancer is prevalent, regular screening for cervical cancer is required [ 16 ]. According to the ‘The Korea HIV/AIDS Cohort Study’, the positive rate was 6.09% for hepatitis B antigen (HBsAg) and 1.78% for hepatitis C antibody (anti-HCV Ab).…”
Section: Clinical Characteristics Of Hiv Infection In Koreamentioning
confidence: 99%